2014
DOI: 10.1016/j.copbio.2013.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic potential of endophytic bacteria

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
256
0
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 512 publications
(295 citation statements)
references
References 66 publications
3
256
0
16
Order By: Relevance
“…Various studies in the literature have reported that rhizospheric microorganisms, especially rhizobacteria, show excellent results in promoting plant growth (Ahemad and Kibret, 2014;Lugtenberg and Kamilova, 2009;Myresiotis et al, 2014;Prashar et al, 2014). Another extensively studied group is the endophytic microorganisms, similar to the rhizobacteria, with the potential for use in various other economic crops (Brader et al, 2014;Hallmann et al, 1997;Rosenblueth and Martinez Romero, 2006;Shen et al, 2014). Yeasts are unicellular fungi that can also be found in the rhizosphere of plants, but in smaller numbers compared to bacteria and filamentous fungi; however, little information is known about their function in this ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies in the literature have reported that rhizospheric microorganisms, especially rhizobacteria, show excellent results in promoting plant growth (Ahemad and Kibret, 2014;Lugtenberg and Kamilova, 2009;Myresiotis et al, 2014;Prashar et al, 2014). Another extensively studied group is the endophytic microorganisms, similar to the rhizobacteria, with the potential for use in various other economic crops (Brader et al, 2014;Hallmann et al, 1997;Rosenblueth and Martinez Romero, 2006;Shen et al, 2014). Yeasts are unicellular fungi that can also be found in the rhizosphere of plants, but in smaller numbers compared to bacteria and filamentous fungi; however, little information is known about their function in this ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike of pathogenic bacteria these neither show any disease symptom on plant nor change the morphology and internal structure of plants. Association between plants and endophytic bacteria is mediated by organic compounds released from both bacterial and host species (Brader et al, 2014). Endophytic bacteria affect the plant growth through biological nitrogen fixation (Compant et al, 2005a), decreasing plant ethylene level, increasing bioavailability of phosphorus and micronutrients as well and production of volatile organic compounds (Kai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ademais, os endofíticos contribuem para a produção de metabólitos nos vegetais, sobretudo de antimicrobianos em plantas de uso medicinal. Sob esse âmbito, esses microorganismos constituem-se em importante e promissora fonte de prospecção de substâncias bioativas (REINHOLD-HUREK;HUREK, 2011;BRADER et al, 2014).…”
Section: Resultsunclassified